المكيافيلية في الفكر الفلسفي الحديث والمعاصر - بن صابر, محمد; بن حليلم, شوقي (جامعة الوادي - University of Eloued, 2022)
ظهرت المكيافلية في العصر الحديث والمعاصر بحلول عصر النهضة مثلها مكيافيلي السياسي والمؤرخ والفيلسوف كما يسميه فلاسفة الفلسفة الحديثة والمعاصرة، وفي دراستنا لمكيافيلي لا حظنا أن القوة هي الهدف الأسمى في فلسفته السياسية حيث تكون القوة هي القيمة العليا التي تستحق الاعتبار عنده. إن معالم المكيافلية اتضحت أكثر في الإشارة إلى الدولة القومية، حيث يتحدث مكيافيلي عن القيم الأخلاقية والسياسية الواجب توفرها في الحاكم ولقد تميز بالواقعية هذا ما جعل أفكاره تتجسد منها فصل الدولة عن الأخلاق والدين ويعتبر ذلك من الأهداف التي سعى اليها في فلسفته. ومن هنا تأثر فلاسفة العصر الحديث والمعاصر بفلسفته عظيم الأثر، منهم توماس هوبز، جون لوك، جون جاك روسو، مونتسكيو، غرامشي، ميرلوبونتي، ميشال فوكو، جاك دريدا، لويس ألتوسير. Abstract: Machiavellian appeared in modern and contemporary times by the renaissance like Machiavelli, a politician, historian and philosopher, as he calls philosophers of modern and contemporary philosophy, and in our study of Machiavelli, we observed that power is the supreme goal in his political philosophy, where power is the supreme value that deserves for has consideration. The contours of social evident more in reference to the state where Machiavelli for moral values and political to be provided in the case, and I tend realistic and that’s what made his thoughts go of the state from morality and religion is considered that the goals sought in philosophers of the modern and contemporary era were influenced by his philosophy, including Thomas Hobbes , john Locke, jean Jacques Rousseau, Montesquieu,Gramsci,merleponte ,Michel Foucault, Jacques derrida and Louis tousseur.
مقال
Keywords: قيم ؛ فلسفة سياسية ؛ دولة ؛ أخلاق ؛ دين; Values; political philosophy; modern; morality; religion